Study of soil erosion risk in the basin of Northern Al-Kabeer river at Lattakia-Syria using remote sensing and GIS techniques - Barakat , M.; Mahfoud , I.; Kwyes, A.A. (Mesopotamian Journal of Marine Sciences, 2022)
Soil erosion is the most importantchallenge foragriculturepresently onthe Syrian coast, especially in areas close to rivers and lakes.This study is to produce a soil erosion risk map based on the COoRdination of Information on the Environment (CORINE) model for the Northern Al-Kabeer River, Lattakia Province.To achieve this objective, the first phase of the study evaluated the soil erosion potential, by estimating soil texture, soil depth and granulometry. Soil was classified according to its erosion potential. A soil erosion potential map was obtained from data on soil erodibility, erosivity and slope.A land cover map of the study area was produced and classified into two classes according to soil protection. A risk map of soil erosion was prepared from information on land cover and potential risk erosion classes obtained previously.The results showed that 2.47% of the study area is in high risk soil erosion areas, 22.18% in moderate risk areas, and 75.35% in low risk areas. The high risk erosion areas were mainly located in the center and northern location within the study area. This study also confirms that land cover is the highest determinant of soil erosion.Land cover accounted for 60.93% of the erosion risk.